Bionic skin model for drug transdermal release research

Through the combination of electrospinning technology and polysaccharides, proteins or phospholipid materials, a bionic skin model with a dynamic interpenetrating network structure was constructed, solving the problems of high cost and large data differences in traditional animal skin models, and achieving drug penetration curves closer to human skin and higher research accuracy.

CN119832794APending Publication Date: 2025-04-15CHINA PHARM UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510208992.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, traditional animal skin models have problems such as high cost, difficulty in separation of stratum corneum, obvious species differences, in reusable, difficult to preserve, and large differences in experimental data in the study of transdermal release of drugs. It is urgent to develop new skin model alternatives.

Method used

The epidermis layer is constructed through electrospinning technology, and the dermis layer is constructed by combining methacrylated hyaluronic acid or its complex, sodium alginate, gelatin or its derivatives and other materials to form a hydrogel scaffold with a dynamic interpenetrating network structure, simulating the structure and barrier function of human skin.

Benefits of technology

This bionic skin model significantly improves the drug's hindering ability, is closer to the penetration curve of human skin, has good reproducibility and reliability, is suitable for the study of drug transdermal release behavior, and shows excellent accuracy and repeatability in topical preparation prescription screening, pharmacological and toxicological research, etc.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119832794A_ABST
    Figure CN119832794A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of biomedical materials and tissue engineering, in particular to a bionic skin model for drug transdermal release research. The hydrogel has skin-like epidermis and dermis structures, the epidermis structure is composed of an electrostatic spinning high-molecular polymer, and the dermis structure is composed of an interpenetrating hydrogel skeleton formed by interweaving polysaccharide, protein and lipid. By adjusting the thickness and composition of the bionic skin, the bionic skin can show a transdermal drug release behavior similar to that of traditional in-vitro skin (such as pigskin, human skin and rat skin) in drug transdermal penetration research, so that the bionic skin is suitable for research on transdermal penetration and absorption behaviors of drugs in external preparations such as ointment, patches and skin care products; and an alternative scheme which is more consistent with ethics, stable, economic and good in reproducibility is provided for prescription screening, quality evaluation and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical materials and tissue engineering, and in particular to a bionic skin model for drug transdermal release research. Background Art

[0002] In the pharmaceutical and cosmetic industries, topical preparations, cosmetic additives or active ingredients are often extensively tested before they are applied to human skin. In addition, the in vitro critical quality attributes of new products must also be evaluated at an early stage. In vitro permeation testing (IVPT) is an indispensable part of the development process of topical skin preparations. It simulates the penetration of drugs through the skin under physiological conditions to ensure the safety and efficacy of the preparation. It is a key method for early compound screening, bioequivalence and bioavailability evaluation.

[0003] According to the current academic consensus and guiding standards at home and abroad, IVPT skin models usually use ex vivo skin, such as human skin or pig skin. However, since the release of my country's first experimental animal regulations in 1988, the ethics of animal experiments have been gradually strengthened, and traditional animal skin models face a series of challenges, including high cost, difficulty in separating the stratum corneum, obvious species differences, inability to reuse, difficulty in preservation, and large differences in experimental data. Therefore, there is an urgent need to develop new alternative skin models.

[0004] In recent years, with the cross-integration of multiple disciplines such as materials science, medicine, biology, engineering and molecular science, tissue engineering technology has provided a new solution to this problem. Through advanced technologies such as freeze drying, 3D printing, electrospinning and microfluidic systems, combined with elements such as skin cells, growth factors and biomaterials, researchers have successfully constructed customized bionic skin models. These bionic skins provide new research ideas for studying the penetration behavior of drugs in the skin and have broad application prospects.

[0005] Currently, bionic skin models can be roughly divided into two categories, namely, cellular skin equivalents and artificial skin models (without cell membranes). Although cellular skin equivalents have biological relevance to human or animal skin, especially in the cosmetic field, there are already marketed products, such as DRT, Pelnac TM , BTM, and However, due to the lack of tight junctions in its fine structure, differences in lipid composition and loss of related cell appendages, the drug permeability in this model is too high, about 4 to 8 times that of human or animal skin, which may lead to some false positive phenomena in toxicity studies. In addition, due to defects such as time-consuming culture, high cost, inability to maintain cell culture for a long time, and sensitivity to the incorporation of chemical absorption enhancers and surfactants, it is difficult to use it for the study of the transdermal behavior of drugs or preparations.

[0006] In contrast, acellular artificial skin models have obvious advantages in long-term stability, easy storage and operation, and generally have better reproducibility and reliability. However, the main problem of this type of skin model is still the lack of structural similarity between acellular membranes and human skin, which leads to large differences in drug permeability, which may be as high as 8 to 10 times, even higher than the difference between cell-containing skin equivalents and human skin. Summary of the invention

[0007] Purpose of the Invention

[0008] In order to overcome the shortcomings and deficiencies of the prior art, the present invention provides an innovative cell-free membrane bionic skin model, which simulates the epidermis by electrospinning such as polyurethane membrane (EPM), and uses methacrylated hyaluronic acid or its complex, sodium alginate (SA), gelatin (Gel) or its derivatives (such as methacrylated gelatin (GelMA) cross-linked hydrogel to simulate the dermis, which more realistically reproduces the structure and barrier function of human skin, shows good correlation with ex vivo pig skin, and can also customize different types of skin according to needs, showing the accuracy and repeatability of the experiment, which is suitable for the study of drug transdermal release behavior, and can be applied to the screening of external preparation prescriptions, pharmacological and toxicological studies, release analysis of harmful ingredients in cosmetics, and research on skin morphology and physiology.

[0009] Technical Solution

[0010] A bionic skin model for drug transdermal release research uses polysaccharides, proteins or phospholipids with different properties to form a hydrogel scaffold with a dynamic interpenetrating network structure through photocuring, ion cross-linking and enzyme coupling reactions. Combined with an electrospun polymer membrane, a bionic skin that can simulate both the dermal matrix and the epidermal barrier is constructed.

[0011] The details are as follows:

[0012] The present invention discloses a bionic skin model for drug transdermal release research, characterized in that the bionic skin comprises an epidermis layer and a dermis layer; wherein the dermis layer comprises a hydrogel polysaccharide material, a hydrogel protein material and a hydrogel phospholipid material;

[0013] The hydrogel polysaccharide material is selected from one or more of the following and their derivatives: hyaluronic acid, sodium alginate, chitosan, glycosaminoglycan; the dermis hydrogel protein material is selected from one or more of the following and their derivatives: gelatin, collagen; the dermis hydrogel phospholipid material is selected from one or more of the following and their derivatives: phospholipids, phosphatidylcholine, phosphatidylinositol, phosphatidylethanolamine;

[0014] The epidermis layer is composed of electrostatically spun polymers, and the electrostatically spun polymers are selected from one or more of the following and their derivatives: polyurethane, polylactic acid, polycaprolactone, zein, polysulfone, polyethersulfone or nylon.

[0015] The present invention also discloses a method for preparing a bionic skin model for drug transdermal release research, which is prepared according to the following steps:

[0016] (1) Preparation of bionic dermis

[0017] A. Synthesis of methacrylated hyaluronic acid or gelatin: add methacrylic anhydride to hyaluronic acid or gelatin solution, adjust pH with NaOH, allow ethanol to settle after the reaction is complete, dry the precipitate, redissolve, dialyze and freeze-dry;

[0018] B. Preparation of methacrylated hyaluronic acid-phospholipid complex: weigh phospholipid, dissolve in anhydrous ethanol, remove ethanol by rotary evaporation under reduced pressure, add pure water for mechanical stirring and hydration after vacuum drying, perform ultrasonic treatment in an ice bath to obtain a dispersion, add the dispersion to an aqueous solution of methacrylated hyaluronic acid for compounding, and then freeze-dry to obtain a methacrylated hyaluronic acid-phospholipid complex;

[0019] C. dissolving methacrylated gelatin (or its derivatives), adding sodium alginate, methacrylated hyaluronic acid (or methacrylated hyaluronic acid-phospholipid complex), and a photoinitiator to swell and dissolve together to form a hydrogel prepolymer solution, pouring the hydrogel prepolymer solution into a mold, curing it with a UV lamp, then adding a calcium chloride solution for ion crosslinking, and finally adding a crosslinking agent to complete enzymatic crosslinking;

[0020] (2) Preparation of bionic epidermis: polyurethane particles are dissolved in N,N-dimethylacetamide and tetrahydrofuran, the reaction system is heated, and a clarified spinning solution is obtained after ultrasonic treatment. The electrospinning machine parameters are set, and the bionic epidermis is obtained by electrospinning.

[0021] (3) Preparation of bionic skin: The bionic epidermis layer is spread flat on the bottom of the mold, and the hydrogel prepolymer in the bionic dermis layer is cast on the bionic epidermis layer, followed by multiple cross-linking to prepare the bionic skin.

[0022] Preferably, the molecular weight of the hyaluronic acid in step (1) A is 3×10 3 ~1×107 Dalton, the mass volume ratio of hyaluronic acid and methacrylic anhydride is 1g:1~20mL, the pH range is 7.5~9.5, and the molecular weight cutoff of the dialysis bag is 1000~50000 Dalton.

[0023] Preferably, in step (2), the reaction system is heated to 45-75°C, the concentration of the clarified spinning solution is 5%-25%, and the electrospinning machine parameters are: the spinning voltage is 4-30 kV; the feed flow rate of the spinning solution is 0.3-15 mL / min; the distance between the spinning solution injection electrode and the receiving device is 5-40 cm.

[0024] Preferably, the concentration of the photoinitiator in step (1) C is 0.01%wt to 1%wt, and the photoinitiator includes one or more of LAP (phenyl-2,4,6-trimethylbenzoyl phosphate lithium salt), photoinitiator 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methyl benzophenone), photoinitiator 1173 (2-hydroxy-2-methyl-1-phenyl-1-propanone), photoinitiator 819 (phenyl bis(2,4,6-trimethylbenzoylmethyl)), MBF (methyl benzoylformate), DEAPO (4-diethylaminobenzoyldiphenylphosphine oxide), and 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone.

[0025] Preferably, the UV lamp in step (1) C has a wavelength of 365 to 405 nm, and the cross-linking agent is any one or a combination of any two of transglutaminase (mTG), carbodiimide, diamine, epoxy compound, hydroxysuccinimide, glutaraldehyde and genipin. More preferably, the cross-linking agent is transglutaminase.

[0026] The preparation principle of a bionic skin model for drug transdermal release research of the present invention is:

[0027] Bionic skin includes an electrospun epidermis layer and a hydrogel dermis layer. The electrospun epidermis layer is formed by continuously pulling out high molecular polymer fibers from a viscoelastic liquid under the action of an electric field to form an interlaced nano-spinning mesh, simulating the structure of the stratum corneum of human skin. The hydrogel dermis layer is a composite hydrogel formed by three cross-linkings, i.e., a triple cross-linking network:

[0028] The first network is formed by photo-crosslinking of methacrylated hyaluronic acid-phospholipid complex, in which methacrylated hyaluronic acid is synthesized by the esterification reaction of hyaluronic acid and methacrylate. Because it is rich in double bonds, it has photo-crosslinking properties. In the presence of photoinitiator LAP and ultraviolet light, it can be quickly cross-linked to form a hydrogel. The methacrylated hyaluronic acid-phospholipid complex is combined with hyaluronic acid through hydrogen bonds, electrostatics, hydrophobic effects, etc. because phospholipids can be embedded in the network structure of hyaluronic acid or adhere to the surface of the molecule.

[0029] The second network is composed of sodium alginate (SA) and Ca 2+ Ionic crosslink formation occurs, and SA-Ca forms a brittle sacrificial network that breaks before other covalent networks to achieve effective energy dissipation, thereby enhancing mechanical properties.

[0030] The third layer is formed by gelatin and its derivatives under the action of the cross-linking agent microbial transglutaminase, which undergoes enzymatic covalent cross-linking between or within molecules, adding a flexible neutral network to the composite hydrogel.

[0031] Through the compounding of these three natural polymer components and the occurrence of their respective cross-linking reactions, the triple networks are entangled and interpenetrated with each other, obtaining a hydrogel with suitable mechanical strength and certain flexibility, which not only simulates the dermis of the skin in terms of composition, but also simulates the dermis of the skin in terms of structure.

[0032] Compared with the prior art, the innovation and beneficial effects of the present invention are mainly reflected in:

[0033] After the bionic epidermis in the bionic skin model of the present invention is combined with the bionic dermis, the resistance of the bionic skin model to each drug is significantly improved, and it is closer to the cumulative permeation curve of the drug through pig skin. Among them, the bionic skin model PU-HPSG containing hyaluronic acid-phospholipid complex has no significant effect on EP and OXY compared to PU-HSG, but it has a particularly obvious resistance to the hydrophilic drug VB6, making its permeation curve closer to the cumulative permeation curve of pig skin. Specifically: under the cumulative drug permeation amount of 24h, the difference between EP pig skin and bionic skin is 2.34 times, the difference between VB6 bionic skin and pig skin is 1.72 times, and the difference between OXY bionic skin and pig skin is 1.17 times, which is far superior to the existing cell-free artificial skin model (up to 8 to 10 times).

[0034] The appearance of bionic skin can simulate the texture of skin, is flexible and elastic, and has certain tensile and anti-curling properties. In the transdermal permeation of drugs with different properties, it shows a permeation amount close to that of pig skin and similar permeation dynamics behavior. It can also be customized for different types of skin according to needs, with excellent accuracy and repeatability. After freeze-drying and then re-dissolving, it can still maintain the appearance of the freshly prepared bionic skin, providing more industrial possibilities in terms of use and preservation, and has broad application prospects in the screening of external preparation prescriptions, pharmacological and toxicological studies, analysis of the release of harmful ingredients in cosmetics, and research on skin morphology and physiology. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The infrared spectra of HA and HAMA in Example 1;

[0036] Figure 2This is the H NMR spectrum of HA-MA in Example 1;

[0037] Figure 3 The electron microscopy results of the hyaluronic acid-phospholipid complex in Example 2;

[0038] Figure 4 The dissolution states of the hyaluronic acid-phospholipid complex in ethanol (A) and pure water (B) in Example 2;

[0039] Figure 5 This is the infrared spectrum analysis of the bionic epidermis in Example 3;

[0040] Figure 6 The appearance (A), SEM morphology (B) and porosity (C) of the bionic epidermis in Example 3;

[0041] Figure 7 This is an investigation of the permeability of the bionic epidermis with different thicknesses in Example 3, where A is VB6, B is EP, and C is OXY;

[0042] Figure 8 For the investigation of the permeability of the bionic dermis layer in Example 5, A is VB6, B is EP, and C is OXY;

[0043] Fig. 9 This is an investigation on the bionic skin permeability in Example 6, where A is VB6, B is EP, and C is OXY. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further illustrated below in conjunction with the embodiments, which does not limit the present invention in any way. Without departing from the technical solution of the present invention, any modification or change made to the present invention that is easily implemented by a person of ordinary skill in the art will fall within the scope of the claims of the present invention.

[0045] Note: "%" in the examples represents 1g / 100mL

[0046] Example 1: Preparation and characterization of methacrylated hyaluronic acid (HAMA)

[0047] 1. Preparation of methacrylated hyaluronic acid:

[0048] Weigh 1.00g hyaluronic acid, add 100mL pure water, stir to make it swell completely, and obtain a clear and transparent solution. Add 5mL methacrylic anhydride (MA) dropwise under ice bath conditions, adjust the pH range of the solution to 8.5 with 5mol / L NaOH, and react in an ice bath for 24h. After the reaction is completed, the reactants are placed in anhydrous ethanol and placed in a refrigerator for sedimentation. The precipitate is placed in a vacuum drying oven for drying, and then 100mL pure water is added to dissolve it, and a dialysis bag (molecular weight cutoff: 14kDa) is added for 48h of dialysis. The product after dialysis is pre-frozen at -80℃ and freeze-dried to obtain the methacrylated hyaluronic acid synthesis product, which is stored in a refrigerator at -20℃ away from light for later use.

[0049] 2. Characterization of Methacrylated Hyaluronic Acid:

[0050] 2.1 Infrared spectrum analysis: potassium bromide tableting method was used. Appropriate amounts of HA, HAMA and potassium bromide were ground into fine powder and then tableted. The results were detected on an infrared spectrometer with a scanning range of 500-4000cm -1 .

[0051] Depend on Figure 1 It can be seen that the modified HAMAs are roughly consistent with the above inherent stretching vibration bands of HA, indicating that the main structure of HA has not changed after modification. -1 A new absorption vibration characteristic peak is formed nearby, which is the ester bond -C=O- generated by the reaction of acid anhydride and hydroxyl group, indicating that the vinyl group in methacrylic anhydride is combined with the HA main chain, so that the modified HAMA contains double bonds and has photo-crosslinking properties.

[0052] 2.2 H-NMR spectrum analysis: Methacrylated hyaluronic acid (HAMA-5) with a MA:HA feed ratio of 5 ml:1 g was dissolved in deuterated heavy water (D2O) at a concentration of 3 mg / mL. After complete swelling, the test was performed, and unmodified hyaluronic acid (HA) was selected as the control group. The frequency of 400 MHz was used for detection, and the parameters were determined by MestReNova software, and the degree of substitution was calculated by integration.

[0053] Depend on Figure 2 It can be seen that with the D2O peak of δ=4.8ppm as the reference line, HAMA will have two obvious characteristic signal peaks near δ=6.1ppm and 5.6ppm, which are the hydrogen nucleus vibration chemical signals of -C=CH2 in methacrylic anhydride. By performing nuclear magnetic resonance analysis on HAMA-5 samples from different synthetic batches, it was found that the batch differences were small and the degree of substitution was about 35%.

[0054] Example 2: Preparation and characterization of hyaluronic acid-phospholipid complex

[0055] 1. Preparation of hyaluronic acid-phospholipid complex

[0056] Weigh 300 mg of phospholipids, dissolve in 20 ml of anhydrous ethanol, remove ethanol by rotary evaporation under reduced pressure, leave a layer of phospholipid film on the bottle wall, vacuum dry to completely evaporate the ethanol, add 50 ml of distilled water and stir mechanically to hydrate it, ultrasonically crush it in an ice bath for 10 minutes to evenly disperse it, and obtain an aqueous dispersion of phospholipids. Dissolve 100 mg of HAMA in 17 ml of water, add the dispersion to the HAMA aqueous solution obtained in Example 1, and stir at a constant temperature of 37°C for 6 hours to compound. After the complex emulsion is prepared, put it into a large culture dish, freeze it in a freezer, and then put it into the drying bottle of a vacuum freeze dryer in an open state to start freeze drying, and freeze dry it after about 48 hours.

[0057] 2. Characterization of HA-phospholipid complex

[0058] Accurately weigh the mass of the freeze-dried sample of the complex (recorded as m1, and calculate the amount of HAMA and PC in it according to the ratio of the complex, recorded as m HA and m PC ), add anhydrous ethanol, shake in a constant temperature oscillator, so that the PC in the complex that has not been complexed with HAMA is fully dissolved in anhydrous ethanol. Use quantitative filter paper and a glass filtration funnel to perform vacuum filtration, and vacuum dry the ethanol-insoluble matter after filtration to remove the residual anhydrous ethanol. After cooling to room temperature, accurately weigh the mass of this part of ethanol-insoluble matter (recorded as m2), and the reduced weight is the amount of uncomplexed PC (recorded as m3, m3=m1-m2), so the amount of PC complexed with HA is m4=m PC -m3. The recombination rate of PL is: m4 / m PC .

[0059] The experimental results show that the chain length of 5k and 1wDa HAMA is too short to complex with phospholipids, and the complexation rate cannot be calculated. The complexation rate of HAMA with a molecular weight greater than about 700,000 and PC is the highest, which is 53.1±3.5%. Figure 3 As shown, phospholipids have the hydrophobic ends of two long fatty acid chains and the hydrophilic end of the phosphate group. They exist in the form of vesicles in aqueous solution and can be embedded in the network structure of hyaluronic acid or adhere to the surface of hyaluronic acid molecules, combining with HA through hydrogen bonds, electrostatics, hydrophobic effects, etc. Figure 4 The dissolution state of hyaluronic acid-phospholipid complex in ethanol and pure water is described.

[0060] Example 3: Preparation and characterization of bionic epidermal EPM

[0061] 1. Preparation of biomimetic epidermis

[0062] Prepare a spinning solution with a concentration of 15%, weigh the polyurethane particles according to the target concentration, add a stirrer, add 5 mL of N,N-dimethylacetamide and 5 mL of tetrahydrofuran in a fume hood, quickly add the rotor, place it in a 50°C water bath and continue stirring for 6 hours until the PU particles are completely dissolved to obtain a clear and transparent spinning solution, ultrasonicate for half an hour to eliminate bubbles, set the electrospinning parameters, and perform electrospinning.

[0063] 2. Characterization of the biomimetic epidermis

[0064] 2.1 Infrared spectroscopy analysis of bionic epidermis

[0065] The potassium bromide tablet method was used. Appropriate amounts of sample and potassium bromide (KBr) were ground into fine powder and then tableted. The samples were then detected on a TENSOR 27 infrared spectrometer with a scanning range of 500-4000 cm -1 .

[0066] Depend on Figure 5 It can be seen that 3004.0cm -1 The absorption peaks appearing near 1687.7cm are caused by the vibration of the CH bond on the benzene ring, indicating that the polyurethane used contains a benzene ring. -1 The corresponding carbonyl C=O absorption peak of polyurethane is 1096.4 cm -1 It is the stretching vibration peak of the C—O group connecting the hydroxyl group to the carbon atom.

[0067] 2.2 Appearance and SEM morphology of bionic epidermis

[0068] The sample was pasted on the conductive glue on the sample stage and surface gold was sprayed for 90 seconds, and then the porous structure of the hydrogel fiber was observed by field emission high-resolution scanning electron microscopy.

[0069] Depend on Figure 6 It can be seen that the bionic epidermis, namely the electrospun polyurethane membrane (EPM), has a good and smooth morphology, the electrospun fibers have no beading phenomenon, the average diameter is 1716±564nm, and the porosity is 20.89±2.90%.

[0070] 2.3 Investigation of the permeability of the bionic epidermis

[0071] By changing the spinning time of fixed concentration spinning solution and the thickness increase of PU film, six parallel groups were set for each concentration. Logan automatic transdermal instrument was used to prepare VB6 (vitamin B6), EP (ethyl hydroxybenzoate) and OXY (oxybutynin) drug-loaded gels. A 24h transdermal permeation evaluation was carried out to explore the influence of different thicknesses on permeability.

[0072] Depend on Figure 7It can be seen that the control is pig skin, VB6 is a hydrophilic drug with a logP of -0.77; OXY is a hydrophobic drug with a logP of 3.78; EP is a drug with moderate hydrophilicity and a logP of 2.03; the hydrophobic bionic epidermis is more permeable to hydrophobic model drugs, but has almost no barrier effect on hydrophilic drugs, but the cumulative permeation of the three model drugs with different Log Ps is significantly reduced with the increase of the thickness of the bionic epidermis, indicating that the thickness of the bionic epidermis can be used to control the speed of drug permeation through the skin, and also indicating that a single layer of bionic epidermis is not enough to simulate the barrier function of the skin, and a combination of bionic dermis is needed to further improve the barrier capacity. A 100μm electrospinning membrane was selected. This thickness was selected considering the production efficiency of the bionic epidermis, and the thickness of the bionic epidermis was not further increased.

[0073] Example 4: Preparation of biomimetic dermal layer HPSG

[0074] Weigh each component material (0.1-2% HAMA-PC (obtained in Example 2), 0.5-2% SA, 1-20% Gel) accurately according to the proportion, add to a 50 mL EP tube, add the photoinitiator LAP powder, add 21 mL of pure water, stir to make each material evenly dispersed, and then place at 40°C to swell for 6 hours. Pour the hydrogel prepolymer solution into a 7×10 cm 2 In the mold, eliminate the bubbles in the solution and set aside. After three cross-linkings in sequence, specifically: the first cross-linking: place a rectangular UV lamp with a band of 405nm vertically on the well plate containing the hydrogel prepolymer solution, turn on the switch, and irradiate for 10s to obtain the first layer of UV-cured molded hydrogel. The second cross-linking: use 2% (w / v) CaCl2 solution to completely immerse the hydrogel, let it stand for 1h, and complete the second layer of ionic cross-linking. The third cross-linking: prepare mTG solution (concentration of 10U mTG / g gelatin), pass through a 0.45μm microporous filter membrane to remove the insoluble flocculent enzyme starch carrier, and use mTG to completely immerse the hydrogel. Finally, place the entire well plate in a 50°C water bath to react for 2h to complete the third layer of enzymatic cross-linking. After washing with pure water, use filter paper to absorb the residual moisture on the surface to obtain the bionic dermis HPSG

[0075] Comparative Example 1: Preparation of bionic dermal HSG

[0076] The preparation method of the bionic dermis HSG of Comparative Example 1 is different from that of the bionic dermis HPSG of Example 4 in that methacrylated hyaluronic acid is used instead of methacrylated hyaluronic acid-phospholipid complex. The remaining steps are the same as those of Example 4.

[0077] Example 5: Investigation of the permeability of bionic dermis

[0078] A Logan automatic transdermal instrument was used to prepare VB6, EP and OXY drug-loaded gels according to Table 2. Six parallel groups were set for each concentration. The bionic dermis HPSG and HSG prepared in Example 4 and Comparative Example 1 were evaluated for 24h transdermal permeation.

[0079] Depend on Figure 8 It can be seen that for model drugs with larger logP values, the release curves of EP and OXY on the bionic dermis are more similar to those on pig skin. Compared with HSG, HPSG significantly increased the permeation resistance to the hydrophilic drug VB6 due to the addition of phospholipids, and the cumulative permeation volume in 24 hours was significantly reduced, which had a certain effect on the permeation of EP, but had almost no effect on the permeation of the hydrophobic drug OXY. This may be because the hydrophobic part of phospholipids repel the polar part of hydrophilic drugs, thereby limiting the permeation of VB6. For hydrophobic drugs, since the hydrophobic part of phospholipids is similar to the molecular structure of OXY, the interaction between the two is weak, so the addition of phospholipids has almost no effect on the permeation of OXY. These characteristics make HPSG more advantageous in meeting the drug barrier function.

[0080] Example 6: Construction of bionic skin PU-HPSG and investigation of its permeability

[0081] 1. Construction of bionic skin

[0082] The bionic epidermis layer (thickness: 100 μm) prepared in Example 3 was placed on a 7×10 cm 2 The bottom of the mold was gently kneaded and pressed to make it flat, and the wrinkled parts were adjusted. The bionic dermis layer was prepared in the mold covered with the bionic epidermis layer according to Example 4 and Comparative Example 1. After the triple cross-linking was completed, the residual moisture on the surface was absorbed by filter paper after washing with pure water, and the bionic skin model PU-HPSG (containing hyaluronic acid-phospholipid complex) and PU-HSG (methacrylated hyaluronic acid) were obtained.

[0083] 2. Investigation of bionic skin permeability performance

[0084] A Logan automatic transdermal instrument was used to prepare VB6, EP and OXY drug-loaded gels according to Table 2. Six parallel groups were set for each concentration. The bionic skin PU-HPSG (containing hyaluronic acid-phospholipid complex) and PU-HSG prepared in Example 6 were evaluated for 24h transdermal permeation.

[0085] Depend on Fig. 9It can be seen that after the bionic epidermis is combined with the bionic dermis, the resistance of the bionic skin model to various drugs is significantly improved, which is closer to the cumulative permeation curve of drugs through pig skin. Among them, the bionic skin model PU-HPSG containing hyaluronic acid-phospholipid complex has no significant effect on EP and OXY compared with PU-HSG, but has a particularly obvious resistance to the hydrophilic drug VB6, making its permeation curve closer to the cumulative permeation curve of pig skin.

[0086] After calculation, the cumulative drug permeation within 24 hours was 2.34 times that of EP pig skin and bionic skin, 1.72 times that of VB6 bionic skin and pig skin, and 1.17 times that of OXY bionic skin and pig skin, which are far superior to the existing cell-free artificial skin model (up to 8 to 10 times).

Claims

1. A bionic skin model for drug transdermal or drug release research, characterized in that: The bionic skin comprises an epidermis and a dermis; wherein the dermis is composed of a hydrogel polysaccharide material, a dermis hydrogel protein material and a dermis hydrogel phospholipid material; the dermis hydrogel polysaccharide material is selected from one or more of the following and their derivatives: hyaluronic acid, sodium alginate, chitosan or glycosaminoglycan; the dermis hydrogel protein material is selected from one or more of the following and their derivatives: gelatin or collagen; the dermis hydrogel phospholipid material is selected from one or more of the following and their derivatives: phospholipids, phosphatidylcholine, phosphatidylinositol or phosphatidylethanolamine; The epidermis layer is composed of electrostatically spun polymers, wherein the electrostatically spun polymers are selected from one or more of the following and their derivatives: polyurethane, polylactic acid, polycaprolactone, polysulfone, polyethersulfone, nylon, zein or silk fibroin.

2. The bionic skin model for drug transdermal or drug release research according to claim 1, characterized in that: The dermis hydrogel polysaccharide material is hyaluronic acid or sodium alginate; the dermis hydrogel protein material is gelatin; the dermis hydrogel phospholipid material is phospholipid; and the epidermis electrostatic spinning high molecular polymer is polyurethane.

3. A bionic skin model for drug transdermal or drug release research according to claim 2, characterized in that: Prepare as follows: 1) Preparation of bionic epidermis: polyurethane particles are dissolved in N,N-dimethylacetamide and tetrahydrofuran, the reaction system is heated, and a clarified spinning solution is obtained after ultrasonic treatment, and the electrospinning machine parameters are set to obtain a bionic epidermis by electrospinning; 2) Preparation of bionic dermis layer: dissolving gelatin, adding hyaluronic acid-phospholipid complex, swelling and dissolving sodium alginate and photoinitiator together to form hydrogel prepolymer solution, pouring the hydrogel prepolymer solution into a mold, curing with ultraviolet lamp, adding calcium chloride solution for ion crosslinking, and finally adding crosslinking agent to complete enzymatic crosslinking to obtain bionic dermis layer; wherein: preparation of hyaluronic acid-phospholipid complex: weighing phospholipid, dissolving in anhydrous ethanol, removing ethanol by rotary evaporation under reduced pressure, vacuum drying, adding pure water for mechanical stirring and hydration, ice bath ultrasonication to obtain dispersion, adding the dispersion to the prepared methacrylated hyaluronic acid dissolved aqueous solution for compounding, and then freeze drying to obtain hyaluronic acid-phospholipid complex; 3) Preparation of bionic skin: firstly spread the bionic epidermis layer on the bottom of the mold, and then cover the bionic dermis layer on the bionic epidermis layer to obtain the bionic skin.

4. The bionic skin model for drug transdermal or drug release research according to claim 3, characterized in that: The molecular weight of hyaluronic acid in step 1) is 3×10 3 ~1×10 7 Dalton, the mass volume ratio of hyaluronic acid or gelatin to methacrylic anhydride is 1g:1~20mL, the pH range is 7.5~9.5, and the molecular weight cutoff of the dialysis bag is 1000~25000 Dalton.

5. The bionic skin model for drug transdermal or drug release research according to claim 3, characterized in that: In step 1), the reaction system is heated to 45-75° C., the concentration of the clarified spinning solution is 5%-25%, and the electrospinning machine parameters are: the spinning voltage is 4-30 kV; the feed flow rate of the spinning solution is 0.3-15 mL / min; the distance between the spinning solution injection electrode and the receiving device is 5-40 cm.

6. The bionic skin model for drug transdermal or drug release research according to claim 3, characterized in that: The concentration of the photoinitiator in step 2) is 0.1%wt to 5%wt, and the photoinitiator includes one or more of phenyl-2,4,6-trimethylbenzoyl lithium phosphate, 2-hydroxy-4'-(2-hydroxyethoxy)-2-methyl benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, phenyl bis(2,4,6-trimethylbenzoylmethyl), methyl benzoylformate, 4-diethylaminobenzoyldiphenylphosphine oxide, and 2-hydroxy-1-[4-(2-hydroxyethoxy)phenyl]-2-methyl-1-propanone.

7. The bionic skin model for drug transdermal or drug release research according to claim 3, characterized in that: The ultraviolet lamp in step 2) has a wavelength of 365 to 405 nm, and the cross-linking agent is any one or a combination of any of transglutaminase, carbodiimide, diamine, epoxy compound, hydroxysuccinimide, glutaraldehyde and genipin. More preferably, the cross-linking agent is transglutaminase.

8. The bionic skin model for drug transdermal or drug release research according to claim 7, characterized in that: Preparation of bionic dermis: 0.1-1% hyaluronic acid-phospholipid complex, 0.5-2% sodium alginate, 5-20% gelatin were added to a 50 mL EP tube, and then 0.01-0.1% photoinitiator phenyl-2,4,6-trimethylbenzoyl phosphate lithium salt powder was added, and 21 mL of pure water was added dropwise. After stirring to make each material evenly dispersed, it was placed at 40°C to swell for 6 hours to form a hydrogel prepolymer solution; the hydrogel prepolymer solution was poured into a 7×10 cm 2 In the mold, eliminate the bubbles in the solution and set it aside; undergo three cross-linking steps in sequence, specifically: the first cross-linking: place a rectangular UV lamp with a wavelength of 405 nm vertically on the well plate containing the hydrogel prepolymer solution, turn on the switch, and irradiate for 10 seconds to obtain the first layer of UV-cured molded hydrogel; the second cross-linking: use a 2% w / v CaCl2 solution to completely immerse the hydrogel, let it stand for 1 hour, and complete the second layer of ionic cross-linking; the third cross-linking: prepare a concentration of 10U mTG / g gelatin, pass it through a 0.45μm microporous filter membrane to remove the insoluble flocculent enzyme starch carrier, and use glutamine transferase mTG to completely immerse the hydrogel; finally, place the entire well plate in a 50°C water bath for reaction for 2 hours to complete the third layer of enzymatic cross-linking, wash with pure water and then use filter paper to absorb the residual moisture on the surface to obtain the bionic dermis; Preparation of bionic epidermis: prepare a spinning solution with a concentration of 5-20%, weigh polyurethane particles according to the target concentration, add a stirrer, add N,N-dimethylacetamide and tetrahydrofuran in a fume hood, place in a 50°C water bath and stir continuously for 6 hours until the PU particles are completely dissolved to obtain a clear and transparent spinning solution, perform ultrasound for half an hour to eliminate bubbles, set electrospinning parameters, and perform electrospinning to obtain a bionic epidermis; Preparation of bionic skin: The bionic epidermis with a thickness of 100 microns was placed on a 7×10 cm 2 The bottom of the mold was gently kneaded and pressed to make it flat and adjust the wrinkled parts; the bionic dermis layer was prepared in the mold covered with the bionic epidermis layer. After the triple cross-linking was completed, the residual water on the surface was absorbed by filter paper after washing with pure water to obtain the bionic skin model.

Citation Information

Cited By

  • Method for simultaneously detecting residual quantity of 1-vinyl-2-pyrrolidone and photoinitiator 2959 in medical material

    CN121027351A

  • Preparation method of bionic cuticle and bionic skin with tissue differentiation-like structure

    CN121495183A